Effect of 30% hydrogen peroxide on marginal integrity of silorane-based versus methacrylate-based composite restorations. - Sedighe Sadat Hashemikamangar; Maryam Ghavam; Nazanin Mahinfar; Mohammad Javad Kharazi Fard (Tehran University of Medical Sciences, 2014)
The aim of this study was to assess the effect of 30% hydrogen peroxide on the microleakage of class V cavities restored with either a silorane-based composite or two methacrylate-based composites.A total of 96 standard class V cavities (1.5 × 2 × 3 mm) were prepared on the buccal surface of sound extracted human premolars with both enamel and dentin margins and randomly assigned into three groups of Filtek P90 (group A) with its respective bonding (P90 system adhesive), Filtek Z250 (group B) and Filtek Z350XT (group C), both with Adper Prompt L-Pop bonding. The teeth were subjected to thermocycling (1000×, 5-55ºC) and half of them randomly underwent bleaching (30% hydrogen peroxide, 15 min, three times), while the remaining half (control) were not bleached. Dye penetration was measured following immersion in 2% basic fuchsin for 24 h. Data were statistically analyzed using Kruskal-Wallis and Mann-Whitney U tests at 95% CI.No significant differences were found between the composites in the control groups in enamel (P=0.171) or dentin (P=0.094) margins. After bleaching, microleakage of Z250 (at the occlusal (P=0.696) or gingival (P=0.867) margins), Z350 (at the occlusal (P=0.323) margin) and P90 (at the occlusal (P=0.316) or gingival (P=0.281) margins) did not change significantly.No significant differences were noted between the bleached and control subgroups of Z250 and P90 in enamel or dentin margins. Microleakage of Z350 composite was reduced at the gingival margin compared to the control group, but no significant difference was observed at the occlusal margin. Microleakage of silorane-based composite in gingival margin was significantly more than two metacrylate-based composites.